Jigsaw Puzzle Inspired Patterning of Gas Diffusion Layers for Enhanced Water Management in Polymer Electrolyte Fuel Cells - Can, Enes Muhammet; Nishihara, Masamichi; Sasaki, Kazunari; Lyth, Stephen Matthew (Wiley, 2025)
Under high current density operation, water generation at the cathode of polymer electrolyte fuel cells (PEFCs) floods the electrode, resulting in severe mass transport limitation and an associated voltage drop. Water management is thus of crucial importance in improving the overall performance of fuel cell systems. Gas diffusion layers (GDLs) with independent pathways for either gaseous oxygen or liquid water transport present a potential solution to this issue. Here a novel, simple, and scalable method is presented for inducing patterned hydrophobicity into GDLs. Hydrophilic GDLs are prepared by immersion of commercial hydrophobic GDLs in hydrogen peroxide. Circular disks are then punched from these using a precision die-cutter. Meanwhile, an array of corresponding holes is punched into conventional hydrophobic GDLs. The hydrophilic disks are then pressed into the holes of the hydrophobic GDL and held in place via friction locking, analogous to completing a jigsaw puzzle. This Jigsaw Puzzle Inspired Patterning (JPIP) technique creates precisely patterned hydrophilic domains to act as dedicated water channels, with separate hydrophobic domains for unhindered gas transport. The use of JPIP GDLs dramatically improves fuel cell performance under high current density operation, with important implications for decarbonization via the hydrogen economy.
Keywords: fuel cell; gas diffusion layer; hydrophobicity; microporous layer; water management